Autophagy Upregulates miR-449a Expression to Suppress Progression of Colorectal Cancer - Lan, Sheng-Hui; Lin, Shu-Ching; Wang, Wei-Chen; Yang, Yu-Chan; Lee, Jenq-Chang; Lin, Pei-Wen; Chu, Man-Ling; Lan, Kai-Ying; Zuchini, Roberto; Liu, Hsiao-Sheng; Wu, Shan-Ying (Frontiers in Oncology, 2021)
Many studies reported that microRNAs (miRNAs) target autophagy-related genes to affect carcinogenesis, however, autophagy-deficiency-related miRNA dysfunction in cancer development remains poorly explored. During autophagic progression, we identified miR-449a as the most up-regulated miRNA. MiR-449a expression was low in the tumor parts of CRC patient specimens and inversely correlated with tumor stage and metastasis with the AUC (area under the curve) of 0.899 and 0.736 as well as poor overall survival rate, indicating that miR-449a has the potential to be a prognostic biomarker. In the same group of CRC specimens, low autophagic activity (low Beclin 1 expression and high p62 accumulation) was detected, which was significantly associated with miR-449a expression. Mechanistic studies disclosed that autophagy upregulates miR-449a expression through degradation of the coactivator p300 protein which acetylates the transcription factor FoxO1. Unacetylated FoxO1 translocated to the nucleus and bound to the miR-449a promoter to drive gene expression. Either activation of autophagy by the inducer or overexpression of exogenous miR-449a decreases the expression of target gene LEF-1 and cyclin D1, which lead to decreased proliferation, colony formation, migration, and invasion of CRC cells. Autophagy-miR-449a-tartet genes mediated suppression of tumor formation was further confirmed in the xenograft mouse model. In conclusion, this study reveals a novel mechanism wherein autophagy utilizes miR-449a-LEF1-cyclin D1 axis to suppress CRC tumorigenesis. Our findings open a new avenue toward prognosis and treatment of CRC patients by manipulating autophagy-miR-449a axis.